Air pollution, PM2.5 composition, source factors, and respiratory symptoms in asthmatic and nonasthmatic children in Santiago, Chile. (April 2017) - Prieto-Parra, Laura; Yohannessen, Karla; Brea, Cecilia; Vidal, Daniella; Ubilla, Carlos A.; Ruiz-Rudolph, Pablo
Abstract: The objective of this study was to determine the association of respiratory symptoms and medication use and exposure to various air pollutants, PM2.5 components, and source factors in a panel of asthmatic and nonasthmatic children in Santiago, Chile. To this end, 174 children (90 asthmatics and 84 nonasthmatics) were followed throughout the winter months of 2010 and 2011. During the study period, children filled out daily diaries to record respiratory symptoms and medication use. Air pollution data were obtained from government central site measurements and a PM2.5 characterization campaign. PM2.5 source factors were obtained using positive matrix factorization (PMF). Associations of symptoms and exposure to pollutants and source-factor daily scores were modeled separately for asthmatic and nonasthmatic children using mixed logistic regression models with random intercepts, controlling for weather, day of the week, year, and viral outbreaks. Overall, high concentrations of air pollutants and PM2.5 components were observed. Six source factors were identified by PMF (motor vehicles, marine aerosol, copper smelter, secondary sulfates, wood burning, and soil dust). Overall, single pollutant models showed significant and strong associations between 7-day exposures for several criteria pollutants (PM2.5, NO2, O3 ), PM2.5 components (OC, K, S, Se, V), and source factors (secondary sulfate) and coughing, wheezing and three other respiratory symptoms in both in asthmatic and nonasthmatic children. No associations were found for use of rescue inhalers in asthmatics. Two-pollutant models showed that several associations remained significant after including PM2.5, and other criteria pollutants, in the models, particularly components and source factors associated with industrial sources. In conclusion, exposure to air pollutants, especially PM2.5, NO2, and O3, were found to exacerbate respiratory symptoms in both asthmatic and nonasthmatic children. Some of the results suggest that PM2.5 components associated with a secondary sulfate source may have a greater impact on some symptoms than PM2.5 . In general, the results of this study show important associations at concentrations close or below current air quality standards. Graphical abstract: Highlights: Panel study of asthmatic and nonasthmatic children in Santiago, Chile. Six source factors were found, including traffic, wood-burning and industrial. Positive associations were observed both for asthmatics and nonasthmatics. Stronger associations were observed for criteria air pollutants. Some results suggest stronger associations for the secondary sulfate source factor.